Sample Entropy Analysis of Noisy Atrial Electrograms during Atrial Fibrillation - Cirugeda-Roldán, Eva María; Molina Picó, Antonio; Novák, Daniel; Cuesta-Frau, David; Kremen, Vaclav (Computational and mathematical methods in medicine, 2018)
Most cardiac arrhythmias can be classified as atrial flutter, focal atrial tachycardia, or atrial fibrillation. They have been usually treated using drugs, but catheter ablation has proven more effective. This is an invasive method devised to destroy the heart tissue that disturbs correct heart rhythm. In order to accurately localise the focus of this disturbance, the acquisition and processing of atrial electrograms form the usual mapping technique. They can be single potentials, double potentials, or complex fractionated atrial electrogram (CFAE) potentials, and last ones are the most effective targets for ablation. The electrophysiological substrate is then localised by a suitable signal processing method. Sample Entropy is a statistic scarcely applied to electrograms but can arguably become a powerful tool to analyse these time series, supported by its results in other similar biomedical applications. However, the lack of an analysis of its dependence on the perturbations usually found in electrogram data, such as missing samples or spikes, is even more marked. This paper applied SampEn to the segmentation between non-CFAE and CFAE records and assessed its class segmentation power loss at different levels of these perturbations. The results confirmed that SampEn was able to significantly distinguish between non-CFAE and CFAE records, even under very unfavourable conditions, such as 50% of missing data or 10% of spikes.
Keywords: Humans; elektrofyziologické techniky kardiologické; fibrilace síní; Catheter Ablation; Electrophysiologic Techniques, Cardiac; srdeční elektrofyziologie; lidé; Cardiac Electrophysiology; Atrial Fibrillation; katetrizační ablace; entropie; Entropy